"Linguistic Behavior Model" For Foreign Language Learning At Samarinda Ulu International Elementary School In Samarinda City - Amiruddin, Amiruddin; Nurasia Natsir; Andilis Arming Gandini (International Journal of Education, Vocational and Social Science, 2023)
This study aims to describe the process by which children's language develops and discover the obstacles that were found after applying the "linguistic behavior model" in the context of learning a foreign language at Samarinda Ulu International Elementary School in Samarinda City. The study used a quasi-experimental time series design. The study's population consisted of all students at Samarinda Ulu International Elementary School in Samarinda City. While the sample is a subset of the population, it is thought to represent the entire population. Purposive sampling was employed for this study's data collection. The sample inclusion criteria are 30 students from Samarinda International Elementary School who were chosen based on their foreign language knowledge. The linguistic behavior model was utilized to collect data from respondents based on three periods of habituation. The study's findings indicate that there are two stages of language acquisition in the learning of a foreign language by children: the stage of comprehension and the stage of competence. As a result of his experiences, every child naturally acquires the process of understanding. Furthermore, the process of mastering the language begins when the child is able to apply what he or she has learned in accordance with the language's actual function and meaning. The application of the language acquisition model of linguistic behavior through several stages of habituation (1, 2, and 3) can help improve language development in children at Ulu Samarinda International Elementary School, particularly in English learning.